Watermelon Pest Management Strategic Plan (PMSP) - Mark A. Mossler (EDIS, 2005)
Florida ranks first in the U.S. in the production of watermelon, accounting for nearly 20 percent of national production. In 2001-2002, 759 million pounds of watermelon valued in excess of $62 million were produced on 23,000 acres ($2,700/acre). Concentrated production occurs in the southern region of the state during the winter months. As the spring arrives, plantings start northward and scatter out across the state. For this reason, a Pest Management Strategic Plan (PMSP) meeting for the Florida watermelon industry was conducted October 14, 2004 at the UF/IFAS Southwest Florida Research and Education Center in Collier County, Florida. This document is PI-52, one of a series of the Pesiticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.